2020
DOI: 10.1021/jacs.0c01666
|View full text |Cite
|
Sign up to set email alerts
|

An Improved PIII/PV═O-Catalyzed Reductive C–N Coupling of Nitroaromatics and Boronic Acids by Mechanistic Differentiation of Rate- and Product-Determining Steps

Abstract: Experimental, spectroscopic, and computational studies are reported that provide an evidence-based mechanistic description of an intermolecular reductive C−N coupling of nitroarenes and arylboronic acids catalyzed by a redox-active maingroup catalyst (1,2,2,3,4,4-hexamethylphosphetane P-oxide, i.e., 1• [O]). The central observations include the following: (1) catalytic reduction of 1•[O] to P III phosphetane 1 is kinetically fast under conditions of catalysis; (2) phosphetane 1 represents the catalytic resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 149 publications
1
43
0
1
Order By: Relevance
“…[11] Since the early report on nucleophilic C-N addition of aryl magnesium reagents to nitroarenes by the Knochel group, [12] the following pioneering studies from the Baran [13] and Hu [14] groups have successfully demonstrated that nitroarenes are valuable precursor to anilines in organic synthesis. [15] Of particular note is the recent seminal work on organophosphorus [16] and molybdenum [17] catalyzed coupling of nitroarenes with boronic acids, which provides a new, effective process for the C À N bond formation (Scheme 1 b). However, there has been no report on the more economic, direct amination of aryl halides with nitroarenes.…”
mentioning
confidence: 99%
“…[11] Since the early report on nucleophilic C-N addition of aryl magnesium reagents to nitroarenes by the Knochel group, [12] the following pioneering studies from the Baran [13] and Hu [14] groups have successfully demonstrated that nitroarenes are valuable precursor to anilines in organic synthesis. [15] Of particular note is the recent seminal work on organophosphorus [16] and molybdenum [17] catalyzed coupling of nitroarenes with boronic acids, which provides a new, effective process for the C À N bond formation (Scheme 1 b). However, there has been no report on the more economic, direct amination of aryl halides with nitroarenes.…”
mentioning
confidence: 99%
“…In 2017, Radosevich group found out that 1,2,2,3,4,4‐hexamethylphosphetane ( 21a[O] ), catalyzed the deoxygenative N−N bond‐forming Cadogan heterocyclization of o‐nitrobenzaldimine, and its derivatives in the presence of hydrosilane terminal reductant (Scheme a) . A reductive intermolecular C−N coupling of boronic acids and nitroaromatics using common hydrosilane reductants was reported using 21a[O] as catalyst (Scheme b) . Extending the organophosphorus‐catalyzed C−N coupling approach, they have synthesized several azaheterocycles from the reactions of ortho‐functionalized nitroarenes and boronic acid (Scheme c).…”
Section: Geometry Constrained Group 15 Compoundsmentioning
confidence: 99%
“…Very recently, further conditions optimization and detailed mechanistic studies on this reaction were conducted by the same group. [34] The "second-generation" conditions with innocuous PMHS as reductant in cyclopentylmethyl ether (CPME) provides a general improvement in yield (Scheme 21). Notably, a variety of heterocyclic nitroarenes that are challenging under the previous conditions react smoothly with arylboronic acids under the new conditions.…”
Section: Organophosphorus-catalyzed Reductive Cà N Bond Formation Andmentioning
confidence: 99%